Bewertung des Scherfestigkeitsverhältnisses für Schrauben festgelegter Festigkeitsklassen. Issue 4 (2nd April 2019) - Dörre, M.; Glienke, R.; Denkert, C.; Berschneider, G.
Translation abstract: The knowledge of the shear capacity of bolts is essential for the design of shear joints. Preloading of joints in steel constructions is in more than 90 % of cases not necessary [1]. In aircraft construction, bearing type fitted joints are very common. In rail vehicle construction these joints are primarily used for risk class G (low) (DIN 25201‐7 [2]). In machine and plant construction, the bearing type joint is not common, but there is a demand that slip resistant joints are designed for an overload against a shearing/ bolt‐bearing‐stress [3]. In the course of earlier investigations on the shear strength ratio, discrepancies for the design according to the various regulations were determined. For this purpose, the authors of this paper carried out over 500 shear tests. The bolts were tested with the nominal diameters ranging from M8 up to M20 with grade 4.6 to 10.9 to determine the shear strength ratio. The focus was on the influences of the single‐/double shear test arrangement as well on the determination of a suitable method for statistical evaluation of the test results. Finally, recommendations are made for the future calculation of the shear resistance.